PENGARUH KEADILAN ORGANISASIONAL TERHADAP KOMITMEN ORGANISASIONAL DAN TURNOVER INTENTION KARYAWAN PADA PT. BANK RAKYAT INDONESIA - Hutagalung, I Dewa Nyoman; Wibawa, I Made Artha (E-Jurnal Manajemen, 2018)
Turnover Intention can cause losses for companies due to recruitment and selection costs arising from turnover intention, one factor that can reduce turnover intention is organizational justice and organizational commitment. This research was conducted on employees of PT. Bank Rakyat Indonesia Branch of Denpasar Gajah Mada. The purpose of this study is to determine the effect of organizational justice on organizational commitment and turnover intention of non-permanent employees at PT. Bank Rakyat Indonesia Branch of Denpasar Gajah Mada. Samples taken as many as 93 respondents. The method of determining the sample in this study was conducted with nonprobability sampling approach that is purposive sampling. The data were collected by distributing questionnaires using a 5-point likert scale to measure 18 statement items. The analysis technique used is Path Analysis. The result of the analysis shows that organizational justice has positive and significant effect on organizational commitment, organizational justice has negative and significant effect on turnover intention, organizational commitment has a negative and significant effect on turnover intention at PT. Bank Rakyat Indonesia Branch of Denpasar Gajah Mada. Keywords : organizational justice, organizational commitment, turnover intention